2000
DOI: 10.18388/abp.2000_4075
|View full text |Cite
|
Sign up to set email alerts
|

ATP-binding domain of NTPase/helicase as a target for hepatitis C antiviral therapy.

Abstract: To enhance the inhibitory potential of 1-beta-D-ribofuranosyl-1,2,4-triazole-3-carboxamide (ribavirin) vs hepatitis C virus (HCV) NTPase/helicase, ribavirin-5'-triphosphate (ribavirin-TP) was synthesized and investigated. Ribavirin-TP was prepared with the use of modified Yoshikawa-Ludwig-Mishra-Broom procedure (cf. Mishra & Broom, 1991, J. Chem. Soc., Chem. Commun, 1276-1277) involving phosphorylation of unprotected nucleoside. Kinetic analysis revealed enhanced inhibitory potential of ribavirin-TP (IC50=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 33 publications
1
57
1
Order By: Relevance
“…On the other hand the nucleoside analogues inhibit the enzyme activity by blocking the ATP-binding site of helicase resulting in uncoupling the ATPase and helicase activities and therefore operate via interaction with the enzyme. These compounds have been used in previous studies to block the helicase activity of hepatitis C virus (Borowski et al, 1999(Borowski et al, , 2000. It has also been suggested that poxviruses, papovaviruses, some RNA viruses such as West Nile virus, severe acute respiratory syndrome coronavirus and dengue virus encoded viral helicases can be probable antiviral drug targets (Kwong et al, 2005).…”
Section: Helicase As Drug Targetmentioning
confidence: 99%
“…On the other hand the nucleoside analogues inhibit the enzyme activity by blocking the ATP-binding site of helicase resulting in uncoupling the ATPase and helicase activities and therefore operate via interaction with the enzyme. These compounds have been used in previous studies to block the helicase activity of hepatitis C virus (Borowski et al, 1999(Borowski et al, , 2000. It has also been suggested that poxviruses, papovaviruses, some RNA viruses such as West Nile virus, severe acute respiratory syndrome coronavirus and dengue virus encoded viral helicases can be probable antiviral drug targets (Kwong et al, 2005).…”
Section: Helicase As Drug Targetmentioning
confidence: 99%
“…This derivative is able to block the NTPbinding site (IC 50 = 22 μM) and to inhibit the ATPase activity (IC 50 = 17 μM) in a competitive way, but is not able to inhibit the helicase activity at concentration lower than 1 mM [14] The partial unwinding activity mediated by these competitive NTPase inhibitors is common to all members of the class, and the concentrations needed for the helicase inhibition usually exceed the IC 50 value by 3-5 times. At these concentrations, the NTPase activity reached 10-35% of the control [46][47][48]. The basis for the phenomenon remains unclear.…”
Section: Inhibition Of Ntpase Activity By Interference With Ntpmentioning
confidence: 93%
“…Consequently, non-(or slowly) hydrolysable ATP-analogs seemed to be effective tools for inhibiting the helicase activity, like adenosine-5 γ-thiotriphosphate (ATP-γ-S), which is used to determine a low level of unwinding of HCV dsRNA [44,45]. However, ribavirin 5 -triphosphate (RTP), that inhibits the HCV NTPase/helicase by a competitive mechanism in regard to ATP [46], and ribavirin 5 -diphosphate (RDP), both reported in Figure 3, even showing IC 50 values in the micromolar range, demonstrates to determine only a weakly enzymatic inhibition [34]. The same behavior has been put in evidence for paclitaxel, compound structurally nonrelated to NTP.…”
Section: Inhibition Of Ntpase Activity By Interference With Ntpmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in FIG. 5b, assays can be used to identify small-molecule helicase inhibitors that have the following effects: they inhibit NTPase activity by direct competition with NTP binding 69 ; competitively inhibit nucleic-acid binding; inhibit NTP hydrolysis or NDP release by blocking the movement of domain 2; inhibit the process that couples NTP hydrolysis to translocation and unwinding of nucleic acid; inhibit unwinding by sterically blocking helicase translocation 70 ; and inhibit unwinding (reviewed in REFS 14,71). For all these mechanisms, unwinding and binding assays can be deployed.…”
Section: Strategies For Discovering Inhibitorsmentioning
confidence: 99%